Improving Customer Satisfaction Through Service Quality - Putri Nurul Zulia Lubis; Tiara Fitriani Fadilah; Afriani Afriani; Imsar Imsar (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to investigate the influence of service quality on customer satisfaction at UMKM PODOMORO Chicken in Medan City. The research method employed was in-depth interviews with regular customers of the restaurant. The results indicate that service quality encompassing factors such as service speed, staff friendliness, food quality, and cleanliness of the environment significantly impacts customer satisfaction. These findings align with consumer behavior theories that highlight the role of customer experience in shaping brand preferences and loyalty. Practically, the study suggests that UMKM PODOMORO Chicken management should focus on enhancing their service quality to improve customer satisfaction and foster strong customer loyalty. Future research could examine additional factors influencing customer satisfaction in the restaurant industry, and stakeholders in the industry are encouraged to adopt best practices to elevate service quality.